The Black-Scholes type financial models and the arbitrage opportunities - Sukhomlin, Nikolay (2007)
By using the conservation laws concept, we study certain financial models similar to the Black–Scholes model. We show that without complement limitations such models can have two or more volatilities. This fact imposes several intrinsic limitations for the dynamical system parameters in order to guarantee the correct definition.